A Recent Advance in the Closure of Skin Wounds on Fragile Skin. (28th June 2021) - Ko, John; Freed, Jeffrey S.
Abstract : The delicate nature of the skin in elderly patients poses a difficult challenge to healthcare providers. Emergency departments are frequently presented with traumatic skin tears and soft tissue avulsions in this group of patients. Procedures aimed at closure of these types of wounds often result in worsening of the tears. The DermaClip® skin closure device, which can eliminate the need for anesthesia, addresses these disadvantages and allows for atraumatic, cosmetically satisfactory closure in a rapid and efficient manner, saving time, and costs.